2022
DOI: 10.1177/10780874221098951
|View full text |Cite
|
Sign up to set email alerts
|

Walking the Talk: Why Cities Adopt Ambitious Climate Action Plans

Abstract: Why do some municipalities adopt ambitious climate action plans and others do not? This study examines United States cities that have signed the Global Covenant of Mayors for Climate & Energy, to identify the factors that have led some of them (37 percent, 63 cities) to adopt ambitious (Net Zero) climate action plans. It finds that two factors make the most difference: (a) whether the city has a paid city employee (or department) dedicated to environmental/energy management and (b) whether the city has a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Much of the research on intergovernmental transaction costs has explored the costs of delegating bureaucratic authority from the standpoint of the states' relationships with the national government (Epstein & O'Halloran, 1999;Horn, 1995;Rabe, 2011), and more recently the hierarchical complexities of statelocal relations (Bery & Haddad, 2023;Farmer, 2022aFarmer, , 2022bHomsy et al, 2019;Huang & Berry, 2022;Youm & Feiock, 2019). However, the complexities of transaction cost federalism can also manifest in the relationship between the federal and local governments (Farmer, 2015).…”
Section: Transaction Cost Federalism Theoretical Frameworkmentioning
confidence: 99%
“…Much of the research on intergovernmental transaction costs has explored the costs of delegating bureaucratic authority from the standpoint of the states' relationships with the national government (Epstein & O'Halloran, 1999;Horn, 1995;Rabe, 2011), and more recently the hierarchical complexities of statelocal relations (Bery & Haddad, 2023;Farmer, 2022aFarmer, , 2022bHomsy et al, 2019;Huang & Berry, 2022;Youm & Feiock, 2019). However, the complexities of transaction cost federalism can also manifest in the relationship between the federal and local governments (Farmer, 2015).…”
Section: Transaction Cost Federalism Theoretical Frameworkmentioning
confidence: 99%
“…Researchers such as K. C. Seto in 2021 have shown that an NZCC transition is possible by analyzing practice data and policies in various cities [124]. Current perspectives on the transition in the literature fall into four main directions, starting with the conceptual transition, where some researchers suggest that the COVID-19 pandemic and subsequent economic collapse could be seen as an opportunity for NZCCs [125,126], allowing city policymakers to reposition the economy and create a more walkable local city. A fresh perspective was taken to rediscover local parks and electric transportation opportunities, such as e-bikes, bike-sharing, and electric-assisted bikes.…”
Section: Urban Transformationmentioning
confidence: 99%